Periodismo de investigación en el Ecuador caso Dayanna Monroy - Reyna Mayea, Damaris Solange (2021)
Practically this investigation is focused on corruption cases that many Ecuadorian journalists have focused on in their careers, on this side we will mention a particular case that has caused controversy in all Ecuadorians, as is the case of the nationally and internationally recognized journalist Dayanna Monroy who has presented impeccable research work and admired by all. The work consists of describing the current conditions leading to investigative journalism. This exploration will help to understand this type of journalism more fully. The investigation was conducted based on the importance that investigative journalism receives and whether they truly have the freedom to broadcast content without fear of repercussions. The importance in the media and the prominence they review. The journalistic work is identified in the midst of the accusations of both sides in the political sphere, it has been a pending task, which, and thanks to investigative efforts, have opened a series of events that we will mention, threats and self-censorship.